Pendampingan Vaksinasi Aeromonas spp. untuk Meningkatkan Sintasan Lele pada Kelompok Budidaya Ikan Desa Dukuh Waluh Kabupaten Banyumas - Mulia, Dini Siswani; Suwarsito, Suwarsito; Juanita, Juanita; Priyadi, Sugeng (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to improve partners’ knowledge and skills regarding vaccination as an effort to control diseases caused by pathogenic organisms, particularly aeromoniasis, which is induced by Aeromonas spp. The partner group consists of fish farmers in Dukuh Waluh Village, Banyumas Regency. The implementation method employed a participatory approach, consisting of four stages: socialization, training, mentoring, and evaluation. The evaluation instruments included questionnaires and interviews, analyzed using a one-group pre-test and post-test design. The results of this program showed that 85% of partner members understood fish disease management, an increase from 50% (exceeding the 80% target), and 85% were able to comprehend and implement fish vaccination practices, an improvement from 42.5% (also exceeding the 80% target). The activity also proved successful in achieving a fish survival rate of 95% in the vaccinated group—surpassing the target of 80%—while the control group (unvaccinated fish) reached only 50%. Overall, the evaluation results indicate that this community service activity effectively assisted partners in addressing fish disease issues and improving aquaculture production performance.